Exploring Sentence Types Between Hotel Receptionists and Foreign Guests - I Komang Ardana; Putu Agus Murtono (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyze the syntactic structure of sentences in english interactions between hotel receptionists and foreign guests. Specifically, it focuses on identifying sentence types, levels of sentence complexity, and syntactic functions that support professional communication at the reception desk. The data were collected from transcripts of 10 authentic interactions and 10 simulated conversations involving five professional hotel receptionists and five foreign guests with intermediate to advanced english proficiency. A descriptive qualitative approach was employed, with audio recordings transcribed and analyzed to identify dominant syntactic patterns. The results revealed that simple and compound sentences were the most frequently used, particularly in greeting, offering assistance, and clarifying information. Complex sentences appeared more often in handling guest complaints and explaining hotel policies. These findings suggest that mastery of varied syntactic structures enhances communication effectiveness in hospitality services. The study’s results are expected to contribute to the development of teaching materials for reception courses and communication skills training for hotel receptionists in the hospitality industry.